(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Overhydration (OH) remains a recurrent problem in peritoneal dialysis (PD), with deleterious effect in outcomes. Recent evidence suggests a direct relation between OH and increased peritonitis risk. The mechanisms of this connection are not well defined, but gut wall edema and malnutrition are probably involved. Methods. Our aim was to assess OH as a risk factor for peritonitis in patients on PD. Retrospective study was done in a PD program with a bio impedance analysis. The investigator reviewed patient charts and documents. The Fresenius® Body Composition Monitor was used to obtain hydration parameters. OH was considered when Overhydration/Extracellular Water (OH/ECW) parameter was over 15% of the dry weight. The diagnosis of peritonitis was made according to the International Society of Peritoneal Dialysis guidelines. Associations between peritonitis rate and the collected variables were assessed using Chi-square test and Pearson’s correlation. Results. An association between OH and the risk of peritonitis was established. Conclusion. OH is prevalent in our patients undergoing PD and it is a modifiable risk factor for peritonitis. The bio impedance analysis is economical and should be used in association with a physical exam and treatment results to achieve the normo-hydrated status in those patients. DOI: 10.52547/ijkd.5959